Brenner & Rector's the kidney - Taal, Maarten W; Chertow, Glenn M; Marsden, Philip A; Skorecki, Karl; Yu, Alan S. L; Brenner, Barry M; Rector, Floyd C (Elsevier-Saunders, 2012)
The publication focuses on various aspects of kidney diseases. Written for professional public.
Keywords: nefrologie; Kidney Diseases; nemoci ledvin